Earthcomm-based Electronic Module: The Learning Material of Natural Resource Management Wisdom. (April 2018) - Mauliddia, H P; Muryani, C; Rintayati, P
Abstract: The study aims to identify: 1) The need of Earthcomm-based electronic module in the learning material of wisdom in natural resource management, 2) The stages of Earthcommbased electronic module development, and 3) The feasibility of Earthcomm-based electronic module in the learning material of wisdom in natural resource management. This study is a Research and Development (R&D) research with ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Conclusions of the study are that: 1) the students need the Earthcomm-based electronic module, 2) the Earthcomm-based electronic module is adapted with curriculum 2013 and developed by using Flipbook maker application and is packaged in the form of compact disk (CD), 3) the feasibility of Earthcomm-based electronic module according to the experts' team consisting of media experts, material experts and linguists is 84% and according to the students' response is 84%, therefore, it can be said that it is worth to be used.